Response of Nitrate Processing to Bio-labile Dissolved Organic Matter Supply Under Variable Oxygen Conditions in a Sandy Beach Seepage Face - Jiang, Shan; Jin, Jie; Wu, Ying; Zhang, Yixue; Wei, Yongjun; Rocha, Carlos; Ibánhez, Juan Severino Pino; Zhang, Jing (Frontiers in Marine Science, 2021)
Supply of bio-labile dissolved organic matter (DOM) has been assumed to be a key factor for the intensity of nitrate (NO3-) removal in permeable coastal sediments. In the present study, a series of flow through reactor (FTR) experiments were conducted using glucose as a N-free bio-labile DOM source to permeable sediments from a sandy beach seepage face to identify its effect on benthic NO3- removal. The results revealed a shift from the dominance of NO3- production to removal processes when NO3- input concentration increased from 10 to 80 µM under oxic conditions. Sediment microbiota information suggests that nitrification (e.g., Nitrosomonas and Nitrososphaera) and denitrification (e.g. Marinobacter and Bacillus) were dominant pathways for benthic NO3- production and removal in the studied sediment. Compared with the active response of sediment microbiota to NO3- additions, the supply of glucose (approximately 300 μM final concentration added) did not significantly change the NO3- removal efficiency under aerobic conditions (dissolved oxygen saturation approximately 100%). Similarly, an insignificant increase of NO3- removal rate after glucose amendment of the circulating water was obtained when dissolved oxygen (DO) saturation decreased to approximately 70% in the input solution. When DO at the input solution was decreased to 30% saturation (sub-oxic conditions), the removal rate of NO3- in the group amended with glucose increased, suggesting that glucose stimulated denitrifiers. These results revealed that NO3- removal relied mainly on the anaerobic environment at particle surfaces, with a dependence on the sedimentary organic matter as an electron supplier under bulk aerobic conditions, while the bio-labile DOM was consumed mainly by aerobic respiration instead of stimulating NO3- reduction. However, the respiration triggered by the over-supply of bio-labile DOM reduced the DO in the porewater, likely depressing the activity of aerobic reactions in the permeable sediment. At this point, the benthic microbiota, especially potential denitrifiers, shifted to anaerobic reactions as the key to support nitrogen metabolism. The glucose amendment benefited NO3- reduction at this point, under sub-oxic conditions.